Analisis Model ASSURE dalam Pembelajaran SKI Berbasis Digital Storytelling: Penggunaan Plotagon Sebagai Media Interaktif - Zamhariroh, Nazila Mumtaza; Soraya, Irma; Kurjum, Mohammad (Tarbawiyah Jurnal Ilmiah Pendidikan, 2025)
This article analyzes the application of the ASSURE model in the teaching of Islamic Cultural History (SKI) through digital storytelling, using the Plotagon application as an interactive medium. The study adopts a literature review method by examining a range of relevant sources related to the ASSURE model, digital storytelling, and the use of Plotagon in educational contexts. The findings suggest that the ASSURE model offers a systematic framework for planning technology-integrated instruction, beginning with learner analysis, setting clear objectives, selecting appropriate methods and media, effectively utilizing media, and concluding with evaluation. Integrating Plotagon as a digital storytelling tool is theoretically shown to enhance learning motivation, student engagement, and understanding of abstract and historical SKI content. Nonetheless, several challenges are identified, including limited visual assets representing Islamic culture, basic animation capabilities, potential technical issues, and subscription costs that may pose obstacles for some schools. Therefore, creative pedagogical strategies and adequate technical support are needed to maximize the platform’s use in learning. Further empirical research is recommended to evaluate the model’s effectiveness in improving student outcomes and to explore alternative digital storytelling tools that are more culturally representative and cost-effective.